Towards integral binary execution: Implementing oblivious hashing using overlapped instruction encodings - Jacob, Matthias; Jakubowski, Mariusz; Venkatesan, Ramarathnam (2007 ACM Multimedia and Security Workshop, 2007)
Executing binaries without interference by an outside adversary has been an ongoing duel between protection methods and attacks. Recently, an efficient kernel-patch attack has been presented against commonly used self-checking code techniques that use checksumming ahead of execution. While methods based on self-modifying code can defend against this attack, such techniques depend on low-level architectural details and may not be practical in the long run. An alternative defense is to use oblivious hashing (OH). Instead of checking code integrity prior to execution, OH can verify untampered runtime behavior continuously. However, earlier OH approaches have some weaknesses, particularly with binary code: Physical instruction bytes cannot be easily checked during execution, and an attacker may be able to detect and remove OH checks, since OH alone does not provide tamper-resistance or obfuscation. In our approach, we deliberately overlap a program’s basic blocks so that they share instruction bytes. This increases tamperresistance implicitly because malicious modifications affect multiple instructions simultaneously. Also, our scheme facilitates explicit anti-tampering checks via injection of OH instructions overlapped with target code, enabling OH that can verify integrity of both runtime state and executing instructions. Thus, our method addresses anti-checksum attacks without resorting to self-modifying code, and also extends OH to verify physical code, not only program state. In addition, overlapping facilitates resistance against disassembly and decompilation. Our approach works on processor architectures and byte-codes that support variablelength instructions. To our knowledge, this is the first technique that blends tamper-resistance into architecture and therefore significantly improves robustness of binaries.